A lexicalist account of argument structure Template-based phrasal LFG approaches and a lexical HPSG alternative - Müller, Stefan (Language Science Press, 2018)
Currently, there are two prominent schools in linguistics: Minimalism (Chomsky) and Construction Grammar (Goldberg, Tomasello). Minimalism comes with the claim that our linguistic capabilities consist of an abstract, binary combinatorial operation (Merge) and a lexicon. Most versions of Construction Grammar assume that language consists of flat phrasal schemata that contribute their own meaning and may license additional arguments. This book examines a variant of Lexical Functional Grammar, which is lexical in principle but was augmented by tools that allow for the description of phrasal constructions in the Construction Grammar sense. These new tools include templates that can be used to model inheritance hierarchies and a resource driven semantics. The resource driven semantics makes it possible to reach the effects that lexical rules had, for example remapping of arguments, by semantic means. The semantic constraints can be evaluated in the syntactic component, which is basically similar to the delayed execution of lexical rules. So this is a new formalization that might be suitable to provide solutions to longstanding problems that are not available for other formalizations.